Interagency Coordination Drivers, Instruments, and Success Factors: A Systematic Literature Review - Muhamad Imam Alfie Syarien; Ghina Samarah (Puslatbang KDOD Lembaga Administrasi Negara, 2023)
Interagency coordination remains a classic and ever-expansive topic in public administration theory. Often considered the key to successful policy or program implementation, coordination also presents its complexities. Research on this subject continues to evolve regarding its sheer numbers, the diversity of locations, problems, and sectors of concern, and the type of government agencies being the subject. This article employed a systematic literature review to identify and analyze coordination drivers, instruments, and critical success factors associated with coordination. The study focused on original articles published from 2010 to 2021 in relevant journals indexed by Scopus. The review revealed that coordination can be driven by problems, institutions, or a combination of both simultaneously. Coordination instruments may involve one or a variety of interventions from governance and structure, systems and processes, policies and agreements, or the engagement of intermediaries. Factors of institutional settings, managerial capacity, and the accuracy of coordination strategies also determine the success of this intervention.